Post-Positivism and the Tripartite Epistemology of Islamic Knowledge: Toward an Alternative Paradigm of Science - Nasution, Soibatul Aslamiah; Ahida, Ridha; Gucandra, Yudi (El-Rusyd, 2025)
This study examines the epistemological crisis of modern science resulting from the dominance of Western positivism, which tends to separate scientific inquiry from transcendental values. The hegemony of rationalism and empiricism has marginalized spiritual dimensions in knowledge production, leading to epistemic reductionism. Drawing on post-positivist perspectives, particularly the works of Thomas S. Kuhn and Paul Feyer bend, this study explores the relevance of Islamic epistemology as an alternative framework. Using a Systematic Literature Review (SLR) of philosophical and Islamic epistemology literature published between 2020 and 2025, the analysis employs philosophical hermeneutics to examine points of conceptual convergence. The findings reveal a philosophical alignment between post-positivist critiques of rational-empirical dominance and the pluralistic epistemological structure of Islamic knowledge, grounded in Bayani (revelation), Burhani (reason), and Irfani (intuition). This synthesis is further articulated through the integration of Al-Attas’s emphasis on metaphysics and adab and Al-Faruqi’s focus on methodological and curricular reconstruction. The study argues that the tripartite Islamic epistemological framework offers a viable alternative paradigm for addressing the reductionism of modern science. However, further empirical studies are required to assess the applicability of this integrative model within Islamic higher education contexts.